Migrating Possibilities: Jonathan Escoffery's "In Flux" and "Independent Living" - Bhasin, Simar (American Studies in Scandinavia, 2025)
The first- and second-generation immigrant characters in Jonathan Escoffery’s short story collection If I Survive You (2022) struggle to belong as they navigate racism, a precarious existence in a foreign country, and familial conflicts. Both the precarity characteristic of the migrant condition and the histories of colonialism, with its enduring legacy in shaping contemporary migration flows from the so-termed Global South to the North, come to be highlighted by Escoffery through these works of short fiction. The eight stories, though they may be read as parts of a whole, are nonetheless separate, self-contained literary works. It is through his characters and their trajectories that Escoffery critiques institutionalized racism and the facile promises that the term “American dream” embodies. In this article two short stories from If I Survive You, “In Flux” and “Independent Living,” are analyzed with a view to opening up a larger academic discussion on how writers such as Escoffery, reflecting deterritorialization through the form of the short story and the English language, may be seen as opening up the borders of what may be referred to as American literary fiction. The article also explores how the character/narrator Trelawny may be seen as an attempt at autofiction by the author, whose life has followed a similar trajectory, and how that becomes an important aesthetic choice for Escoffery’s politics of literary representation of the transnational Jamaican-American community.